Never tell a lie - Ephron, Hallie (New York, NY : William Morrow, 2008)
Ivy and David Rose, happily married high school sweethearts and expecting their first child, are plunged into a growing web of suspicion when a young, pregnant high school classmate disappears and David's past is exposed in this tale of obsession.
edited hb 2015-06-16
Keywords: Friends -- Fiction; Pregnant women -- Fiction; Suburban life -- Fiction; Domestic fiction